The Influence Of Leadership Style And Organizational Culture On Employee Performance At Pt Laras Karya Kahuripan Pali District - Saputri, Ranti; Naruliza, Esty; Aryanti, Rahmi; Effendi, RY. (Jurnal Fokus Manajemen, 2024)
This study aims to evaluate the influence of leadership style and organizational culture on employee performance at PT Laras Karya Kahuripan, located in PALI Regency. A quantitative approach was used, with data collected through surveys and interviews. The researcher visited the site directly to distribute questionnaires to 171 respondents and conducted an interview with one of the company's employees. The collected data were analyzed using multiple linear regression methods. The results showed that leadership style and organizational culture simultaneously have a significant effect on employee performance, contributing 31.7%, while the remaining 63.3% is influenced by other factors outside the studied variablesThe Fcount value is 40.455>Ftable 2.33 and the significance level is 0.000<0.10 so that the hypothesis H0=is rejected and H1=accepted.